#### Answer

-16$x^{7}$

#### Work Step by Step

(-4$x^{5}$)(4$x^{2}$) = (-4 * 4)($x^{5}$$x^{2}$) = -16$x^{5 + 2}$ = -16$x^{7}$

Published by
Pearson

ISBN 10:
0321671791

ISBN 13:
978-0-32167-179-0

-16$x^{7}$

(-4$x^{5}$)(4$x^{2}$) = (-4 * 4)($x^{5}$$x^{2}$) = -16$x^{5 + 2}$ = -16$x^{7}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.